Clothing Aesthetics: Consistent Colour Choices to Match Fair and Tanned Skin Tones. (November 2021) - Perrett, David Ian; Sprengelmeyer, Reiner
Fashion stylists advise clothing colours according to personal categories that depend on skin, hair and eye colour. These categories are not defined scientifically, and advised colours are inconsistent. Such caveats may explain the lack of formal tests of clothing colour aesthetics. We assessed whether observers preferred clothing colours that are linked to variation in melanin levels among White women. For this, we presented 12 women's faces: six with fair skin (relatively lower in melanin) and six with tanned skin (relatively higher in melanin). Across two experiments, observers ( N  = 96 and 75) selected the colour (hue and saturation or hue and value) of simulated clothing that most suited the skin tone of each face. Observers showed strong preferences for red and blue hues, and in addition favoured 'cool' blue hues to match fair skin and 'warm' orange/red hues to match tanned skin. This finding suggests that skin tone can determine colour preferences for clothes.